11beta-hydroxysteroid dehydrogenase type 1: a tissue-specific regulator of glucocorticoid response. - Tomlinson, J; Walker, E; Bujalska, I; Draper, N; Lavery, G; Cooper, MS; Hewison, M; Stewart, P (2004)
11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) interconverts inactive cortisone and active cortisol. Although bidirectional, in vivo it is believed to function as a reductase generating active glucocorticoid at a prereceptor level, enhancing glucocorticoid receptor activation. In this review, we discuss both the genetic and enzymatic characterization of 11beta-HSD1, as well as describing its role in physiology and pathology in a tissue-specific manner. The molecular basis of cortisone reductase deficiency, the putative "11beta-HSD1 knockout state" in humans, has been defined and is caused by intronic mutations in HSD11B1 that decrease gene transcription together with mutations in hexose-6-phosphate dehydrogenase, an endoluminal enzyme that provides reduced nicotinamide-adenine dinucleotide phosphate as cofactor to 11beta-HSD1 to permit reductase activity. We speculate that hexose-6-phosphate dehydrogenase activity and therefore reduced nicotinamide-adenine dinucleotide phosphate supply may be crucial in determining the directionality of 11beta-HSD1 activity. Therapeutic inhibition of 11beta-HSD1 reductase activity in patients with obesity and the metabolic syndrome, as well as in glaucoma and osteoporosis, remains an exciting prospect.